Predictive effect of molecular and clinical characteristics for the OS and PFS efficacy of anti-PD-1/PD-L1 immunotherapy in patients with NSCLC: a meta-analysis and systematic review - Feng Zhao; Rui An; Liqian Wang; Jikang Shan; Xianjun Wang (BMJ Open)
Objective To evaluate the predictive effect of molecular and clinical characteristics for the efficacy of anti-programmed cell death 1 (PD-1)/programmed cell death ligand-1 (PD-L1) immunotherapy in patients with non-small cell lung cancer (NSCLC).Design Systematic review and meta-analysis.Setting Twelve randomised controlled trials (RCTs) with 7442 patients were retrieved from all over the world.Methods Electronic databases were searched for eligible RCTs. The HRs and 95% CIs for overall survival (OS) and progression‐free survival (PFS) for the whole and subgroup population were extracted for meta-analysis using Review Manager V.5.3 software.Primary and secondary outcome measure OS was the primary outcome and PFS was the secondary outcome.Results Twelve RCTs with 7442 patients were included. For the trial population, anti-PD-1/PD-L1 immunotherapy significantly improved OS (HR=0.78, 95% CI 0.70 to 0.86, p<0.00001) and objective response rate (ORR) (risk ratio=1.37, 95% CI 1.08 to 1.74, p=0.009). Subgroup analysis results showed an improved OS at PD-L1≥1%, ≥5% and ≥50% levels, and a longer PFS at PD-L1≥5% and ≥50% levels. Moreover, OS and PFS benefits were observed in the non-first line treatment, squamous cell carcinoma histology, male, smoking, non-central nervous system (CNS) metastasis, epidermal growth factor receptor (EGFR) wild-type and Kirsten rat sarcoma viral oncogene homolog (KRAS) mutant subgroups.Conclusions Anti-PD-1/PD-L1 immunotherapy significantly improved OS and ORR and reduced the rate of Adverse Events (AEs) compared to chemotherapy. PD-L1 expression, line of therapy, histology, sex, smoking history, CNS metastases, EGFR and KRAS mutational status might be potential predictors for the therapeutic effect of anti-PD-1/PD-L1 immunotherapy in specific patients with NSCLC.